Table S12 from The Spatial Structure of the Tumor Immune Microenvironment Can Explain and Predict Patient Response in High-Grade Serous Carcinoma - Lucy B. Van Kleunen (20104025) (2024)
Table S12. Random forest predictive performance results. Full results for all random forest models using 15 different feature sets. Mean and standard deviation AUC results across 500 evaluations are reported for both OS and PFS.